High-dose administration of tyrosine kinase inhibitors to improve clinical benefit: A systematic review. (June 2021) - Gerritse, Sophie L.; Janssen, Jorien B.E.; Labots, Mariette; de Vries, Ralph; Rudek, Michelle; Carducci, Michael; van Erp, Nielka P.; Verheul, Henk M.W.
Highlights: Resistance to standard dosed TKIs remains a major challenge. At high drug concentrations many TKIs have a broad inhibitory profile. High dose intermittent strategy with multitargeting TKIs leads to high (peak) plasma concentrations. High dose intermittent TKI administration could potentially produce enduring clinical benefit. Abstract: Background: Innovative strategies to fully exploit the antitumor activity of multitargeted tyrosine kinase inhibitors (TKIs) are urgently needed. Higher concentrations of TKIs at their target site, i.e. intratumorally, may lead to broader kinase inhibition, which might be essential for the optimal suppression of tumor growth and induction of apoptosis. To reach these higher intratumoral concentrations, without encountering dose limiting toxicity, alternative TKI dosing strategies employing higher daily and high intermittent doses have been studied. In this systematic review, we evaluated the current clinical evidence to support (intermittent) high TKI dosing regimens. Methods: A systematic review was conducted in the following databases: PubMed®, EMBASE® and Cochrane Library©, to evaluate efficacy of alternatively scheduled high-dosed regimen (a higher dose in a regular daily schedule than registered or a higher dose in an alternative intermittent schedule) of TKIs in (haemato-)oncology. Data were extracted independently by two authors according to predefined criteria. Extracted data were tabulated to summarize key findings. Results: Out of twenty studies that met the inclusion criteria, thirteen investigated higher daily dose schedules of either afatinib, axitinib, erlotinib, gefitinib, imatinib, sorafenib, and sunitinib. Five of these studies included pharmacokinetic analyses, reporting marginal higher maximum drug concentrations (Cmax ) in plasma (1.3–4-fold higher) compared to the standard dose schedules. Seven clinical trials investigated intermittent high-dose schedules requiring treatment breaks, with the following TKIs: afatinib, erlotinib, gefitinib, lapatinib, sorafenib, and sunitinib. Six of these included pharmacokinetic results, all reporting higher (2–21-fold) Cmax in plasma compared to the standard daily dose schedule, with manageable toxicity. No data on tumor concentrations were presented. Data on the efficacy outcomes were limited due to small sample size, study designs, phase 1 population and heterogeneous tumor types. Conclusions: Early phase clinical studies show that high-dose intermittent TKI-treatment schedules can lead to an increased Cmax compared to standard (low-dose) daily administration with manageable toxicity. These higher concentrations are assumed to reflect higher intratumoral concentrations. Further investigation of the potential improvement in clinical benefit of a high-dose intermittent strategy with multitargeting TKIs is warranted.